UNLOCKING LABOR MARKET: THE ROLE OF FDI, EDUCATION, INTERNET USAGE, AND GDP GROWTH IN 5-ASEAN - Latifunisa, Aisyah; Nihayah, Annis Nurfitriana (Politeknik Negeri Ambon, 2025)
Introduction: Labor absorption is a crucial indicator of economic development. The many job gaps indicate that the labor market still has problems. Issues in the labour market arise because there is a mismatch between the demand and supply of labour, so the available labour is not optimally absorbed. This study examined five ASEAN countries: Indonesia, Malaysia, Singapore, the Philippines, and Thailand. The aim is to analyze how the roles of FDI, GDP Growth, Education, and Internet use influence labor absorption in these five ASEAN countries.Methods: This study employs a quantitative approach, utilizing the Data Panel Regression analysis method. Based on the results of the model selection, the model used in this study is the FEM (Fixed Effect Model)Results: The study found that FDI and GDP Growth did not have a significant effect on labor absorption. Meanwhile, Internet Usage harms labor absorption. For education, the mean school years are used to indicate positive and considerable results. Keywords: ASEAN, Education, FDI, Internet Usage, Labor Market, LFPR